2008
DOI: 10.1002/j.1554-7531.2008.tb00349.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Complexation Model and Its Implications for Chemical Phosphorus Removal

Abstract: A phosphate complexation model is developed, in an attempt to understand the mechanistic basis of chemically mediated phosphate removal. The model presented here is based on geochemical reaction modeling techniques and uses known surface reactions possible on hydrous ferric oxide (HFO). The types of surface reactions and their reaction stoichiometry and binding energies (logK values) are taken from literature models of phosphate interactions with iron oxides. The most important modeling parameter is the propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
0
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 18 publications
7
83
0
7
Order By: Relevance
“…Other authors also demonstrated that equilibrium chemistry is not always fully applicable to the precipitation of phosphorus using ferric chloride. In most cases authors are forced to postulate new ferric phosphate species [24], adsorption [23] or complexation mechanisms [26] to better represent their results.…”
Section: Analysis Of Orthophosphate Precipitation Experiments At a Comentioning
confidence: 99%
“…Other authors also demonstrated that equilibrium chemistry is not always fully applicable to the precipitation of phosphorus using ferric chloride. In most cases authors are forced to postulate new ferric phosphate species [24], adsorption [23] or complexation mechanisms [26] to better represent their results.…”
Section: Analysis Of Orthophosphate Precipitation Experiments At a Comentioning
confidence: 99%
“…In orthophosphate removal, co-precipitates are formed between the soluble phosphorus and a metal salt, such as aluminum of iron salts (Smith et al 2008). Solids are removed in with the sludge and taken to landfill .…”
Section: Introductionmentioning
confidence: 99%
“…calcium, magnesium, iron, or aluminum phosphates, or hydroxyphosphates). The direct precipitation of pure ferric phosphate does not appear to occur to any significant extent at pH values above 5 (Takacs et al, 2006;Smith et al, 2008;Szabo et al, 2008). This indicates that the components of pRP can be complex due to different operating conditions and other mechanisms, such as adsorption and co-precipitation of phosphate, can contribute more to the formation of pRP rather than precipitation of ferric phosphate.…”
Section: Removal Of Various P Fractions By Different Treatment Processesmentioning
confidence: 75%